2015
DOI: 10.17826/cutf.87099
|View full text |Cite
|
Sign up to set email alerts
|

Çocukluk Çağında Periferik Lenfadenopatiler: Tek Merkezli Çalışma

Abstract: Cukurova Medical Journal 2015;40(3):418-429. ABSTRACTSPurpose: Lymphadenopathy is defined as an abnormality in the size and/or character of lymph node. In this study we aimed to describe the clinical and laboratory findings of benign and malignant causes of peripheral lymphadenopathy in childhood. Material and Methods: Two hundred and twenty four patients who were admitted to the clinic with peripheral LAP were evaluated. Age, gender, laboratory and radiologic findings, final diagnoses, and duration, localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
1
5
1
4
Order By: Relevance
“…Various studies in the literature reported that lymphadenopathy was more common in the male gender (31). In a study, the mean age of these patients was reported to be 7.4±4.7 years (31). The findings regarding age and gender in our study are compatible with the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Various studies in the literature reported that lymphadenopathy was more common in the male gender (31). In a study, the mean age of these patients was reported to be 7.4±4.7 years (31). The findings regarding age and gender in our study are compatible with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of children under the age of five, lymph nodes were found in 44% of healthy children and 64% of children evaluated for disease (30). Various studies in the literature reported that lymphadenopathy was more common in the male gender (31). In a study, the mean age of these patients was reported to be 7.4±4.7 years (31).…”
Section: Discussionmentioning
confidence: 94%
“…[13] In studies conducted in children of our country, the cancer rate has been reported in a wide range, such as 1-38%. [14][15][16][17][18][19][20][21] Incidence rates of cancer reported from pediatric oncology outpatient clinics range most prevalently between 1, and 38 percent. [14][15][16][17][18][19][20][21] The highest rates (>15%) have been generally reported in studies conducted in pediatric oncology polyclinics.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Incidence rates of cancer reported from pediatric oncology outpatient clinics range most prevalently between 1, and 38 percent. [14][15][16][17][18][19][20][21] The highest rates (>15%) have been generally reported in studies conducted in pediatric oncology polyclinics. [14][15][16][17][18][19][20][21] In a study reporting only the results of patients undergoing biopsy, the rate of cancer reportedly increased up to 40.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation